Tribological properties of a halogen-free ionic liquid for Inconel 690–tungsten carbide contact. (November 2021) - Guo, Bian; Li, Yan; Zheng, Jianming; Li, Feizhou; Li, Xubo; Du, Xin; Yuan, Lei
Abstract: In this study, we synthesized ionic liquids (ILs) P888 P-P8 and P888 P-SP4, and compared their tribological performances with that of C4 Min-PF6 as a lubricant for Inconel 690– tungsten carbide contact. The tribological test results show that IL P888 P-SP4 displays better antifriction and antiwear performances than C4 Min-PF6 and P888 P-P8 at particularly at high temperature of 150 °C. We obtained the lubricating mechanism of IL P888 P-SP4 by conducting scanning electron microscopy, energy dispersion spectrometry, X-ray photoelectron spectroscopy, time of flight-secondary ion mass spectrometry, and transmission electron microscopy analyses. The results indicated that the tribochemical reaction occurred between the ILs and nickel-based alloys, and lubrication films were formed on the friction surface. Highlights: We synthesized a halogen-free IL lubricant (P888 P-SP4 ) for Inconel 690–tungsten carbide contact. IL P888 P-SP4 can significantly enhance the tribological performance of Inconel 690 alloys. Owing to the synergistic effect of S/P in P888 P-SP4, a lubrication film was formed.